(untitled) (Journal of Dentistry and Allied Science, 2024)
The purpose of this study was to prospectively compare electrosurgical pulpotomy with formocresol pulpotomy technique used on children’s primary teeth by evaluating clinical and radiographic success. During the research period, 260 patients were included in the study. It ranges in age from 2 to 10 years. Among the studied patients, electro surgery patient was 140 and formocresol pulpotomy patient was 120. Teeth were evaluated clinically and radiologically after 6, 12 and 18 months. After 12 months postoperative observation time, the clinical and radiographic success rates for the electrosurgery was 89.29% and 80.52% respectively when 67.50% and 59.71% were for the formocresol technique. There was a statistically significant difference between the electrosurgery and formocresol pulpotomy techniques for both clinically or radiographically techniques. Journal of Dentistry and Allied Science, Vol. 7 No 1: 25-28